Xq12q13.2 duplication detected in a child in selective exome screening - A. A. Dokshukina; Je. Shubina; D. N. Maslennikov; I. O. Sadelov; E. R. Tolmacheva; S. V. Ionushene; T. A. Bairova; L. V. Rychkova; D. Yu. Trofimov; D. N. Degtyarev (Acta Biomedica Scientifica, 2024)
Background. Within the framework of the regional pilot project on selective exome screening of newborn children, which is carried out on the basis of the National Medical Research Center for Obstetrics, Gynecology and Perinatology named after Academician V.I. Kulakov, we conducted molecular genetic testing of children who meet the criteria for inclusion in the increased group of hereditary diseases. We examine not only children with suspected genetic etiology of the condition, but also children with borderline clinical and laboratory manifestations and minor developmental anomalies.The aim of the study. To describe the clinical and phenotypic features of a patient with a previously undescribed Xq12q13.2 duplication detected in the neonatal period.Materials and methods. The child was examined within the framework of a regional pilot project on selective exome screening of newborn children. DNA was isolated from a biological sample of venous blood of the newborn, and whole exome sequencing and chromosomal microarray analysis were performed. Signed informed voluntary consent for the publication of the examination data and a photograph of the child were obtained from the legal representatives of the proband.Results. Data in favor of the presence of a previously undescribed Xq12q13.2 duplication, confirmed by the reference method were obtained in a patient included in the project in accordance with the clinical criteria for the formation of a risk group according to the data of the conducted whole exome sequencing. Discussion. Xq12q13.2 duplication was detected in the proband from the present clinical observation with non-specific clinical manifestations in the neonatal period. Similar duplications have been described in the literature in three patients with congenital malformations, epilepsy and psychomotor retardation. Early diagnosis of such a copy number variation disorder before the appearance of severe clinical signs of the disease will allow determining the prognosis and tactics of observation and treatment of the patient.Conclusion. The described case of Xq12q13.2 duplication in a patient demonstrates the importance of timely genetic analysis to optimize medical genetic counseling, reduce diagnostic search and improve prognosis for patients.